Podcasting - audio obsah v digitální éře a jeho posluchači a posluchačky v Česku - Sudíková, Tereza (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2020)
The master thesis entitled "Podcasting - audio content in the digital era and its listeners in Czechia" is devoted to the phenomenon of podcasting which connects the traditional audio format with new digital technologies. It deals with its history and current state both abroad and in Czechia. It also describes the specifics of podcasting, compares it with radio programs, mentions the importance of podcast applications or the funding issue of independent podcasts. It focuses attention on the role of the audience in today's world and the associated concepts of participatory culture and user generated content. The audience is also associated with the uses and gratifications theory which tries to understand why people consume media content. The aim of the research part of the thesis was to obtain information about Czech podcast listeners with whom semi-structured interviews were conducted. The collected data were then processed using the grounded theory method. The findings are organized into five chapters in order to answer five research questions. They revealed the motivations of Czech listeners for listening to podcasts, their perception of podcasts in comparison with radio programs, their attitude to listening to Czech and foreign podcasts, their perception of podcast presenter and their attitude...
Keywords: publikum; audio; on-demand; podcasting; podcast listeners; audience; uses and gratifications theory; posluchači a posluchačky podcastů; teorie užití a uspokojení; podcast